Analyzing the periocular biometric-based access control systems - Mon, Chit Su; Amir Hussin, Amir Aatieff; Sin, Toh Kai (Institute of Physics Publishing, 2020)
Biometrics is a widely studied topic for security applications or identity identification. This project had focused on primarily on studying a small region around the eye known as the periocular region as a supplementary biometric. This is the region that includes eyelids, lashes and eyebrows. A few previous studies had proven that periocular biometrics has applied as an independent recognition system under unconstrained scenarios. The biometric data for this region can be easily obtained with existing setups used face and iris recognition. In this project, the data and information was gathered mainly through two methods which were the observation and review on other documentations related to the system. The qualitative research was performed through observation and surveys related to the system. The samples was obtained in a way that the cooperation from the subject or participant was informal while interaction with the biometric system was facilitated. the prototype generated alternative way to allow access to the system using the periocular biometric.